Penyimpangan terhadap Pasal 5 Ayat (1) Huruf b dan c Peraturan Kejaksaaan Nomor 15 Tahun 2020 tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif terhadap Perkara yang Memiliki Kriteria/Keadaan yang Bersifat Kasuistik - Teza Salih Mauludin; Lies Sulistiani; Ajie Ramdan (CV Rewang Rencang, 2024)
Article 5 Paragraph (1) of Perja 15/2020 is a cumulative principle requirement. However, in certain criminal acts the three principle conditions can be distorted as in Article 5 Paragraph (2), Paragraph (3), and Paragraph (4). This study examines the current regulation of the implementation of deviations from Article 5 Paragraph (1) letter b and c of Perja 15/2020 and the enforcement of law deviations from Article 5 Paragraph (1) Letter b and c of Perja 15/2020 by the public prosecutor. The research method used is juridical normative in the form of an assessment of literature materials or secondary data. The statute approach and the case approach are the two approaches used in this study. To obtain information that supports this study, data collection techniques in the form of interviews were also used. The results showed that currently the implementation of the termination of prosecution deviates from Article 5 Paragraph (1) Letters b and c referring to Perja 15/2020.